KAJIAN TINGKAT INFEKSI NEMATODA USUS PADA MURID SDN NAGARI LIMAU GADANG KABUPATEN PESISIR SELATAN PROVINSI SUMATERA BARAT - Armen, Armen (IAIN Batusangkar, 2012)
The research was done in Nagari Limau Gadang, West Sumatera. The purpose of the research was to study the rate of intestinal nematode infection on the students of SDN Nagari Limau Gadang.The population of the research was the students of SDN Nagari Limau Gadang as many as 100 students divided into six grades, that is grade 1 until grade 6. By using stratified proportional random sampling, 40% of the students on each grade were considered as the sample. The hypothesis of the research was 85% of the students were infected by intestinal nematode and 15% were not. As the result, the hypothesis was accepted; more than 75% of the students of SDN Nagari Limau Gadang in Pesisir Selatan regency were infected by intestinal nematode, especially Ascaris lumbricoides35% and Ancylostoma 8,33%. It was found that intestinal nematode mostly infected female students, the students under 9 years old, and those with uneducated parents. Key words: infection, nematode, student